ANALISIS KINERJA PEGAWAI SUB BAGIAN PENYELENGGARAAN PENGAWASAN DI SEKRETARIAT DPRD KOTA TANGERANG SELATAN - Lazuardini, Aurora; Noer, Khaerul Umam; Mawar, Mawar; Purbaningrum, Dini Gandini (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The performance of a government agency can be seen from the performance of its government employees or apparatus, the author will focus this research on the South Tangerang City DPRD secretariat, where the South Tangerang City DPRD secretariat employees have the main task and that is to facilitate members of the South Tangerang City DPRD. In assessing employee performance, performance appraisal is very important for every employee to measure how employee performance is. This and measure the extent to which the main tasks and functions of the DPRD secretariat can be carried out. The purpose of this study was to find out how the performance of employees at the South Tangerang City DPRD secretariat. The research method used in this study uses a qualitative description approach. Data collection techniques are carried out by means of interviews, observation, and documentation. Using theoretical indicators from Hasibuan which states that employee performance indicators consist of work quality, work quantity, discipline, and responsibility. Based on the results of the study, it can be stated that the work quality of the sub-division for the implementation of supervision is good. Then the quantity of work of employees is good. Furthermore, the discipline of employees of the sub-section of management and supervision is said to be not good. Then the indicators of cooperation carried out by the sub-section of the supervision administration are good. In connection with the last indicator regarding responsibility, the employee of the sub-division for the implementation of supervision is already responsible.